2017
DOI: 10.1016/j.landusepol.2017.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of land urbanization and land finance on carbon emissions: A panel data analysis for Chinese provinces

Abstract: The rapid urbanization in China comes with several economic, social, and environmental issues, most of which are related to land use. This study contributes to research on the land-growth-environment nexus by investigating the effect of land urbanization and land finance on carbon emissions in China from 2004 to 2013 using the Stochastic Impacts by Regression on Population, Affluence, and Technology (STIRPAT) model. Results show that land finance and land urbanization significantly affect carbon emissions. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
77
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(79 citation statements)
references
References 65 publications
1
77
0
1
Order By: Relevance
“…Ouyang and Lin ( 2017 ) studied the relationship between urbanization and carbon emissions in India, China, and Japan. Zhang and Cheng ( 2009 ) and Zhang and Xu ( 2017 ) found a positive correlation between urbanization, energy consumption, and carbon emissions in China from a national perspective. Ding and Li ( 2017 ) used the LMDI decomposition method and found significant regional differences in the influence of urbanization on carbon emissions.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Ouyang and Lin ( 2017 ) studied the relationship between urbanization and carbon emissions in India, China, and Japan. Zhang and Cheng ( 2009 ) and Zhang and Xu ( 2017 ) found a positive correlation between urbanization, energy consumption, and carbon emissions in China from a national perspective. Ding and Li ( 2017 ) used the LMDI decomposition method and found significant regional differences in the influence of urbanization on carbon emissions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As the literature on this grows, scholars are no longer limited to studying how changes in urban and rural population structures affect national carbon emissions; namely, the research has become more comprehensive. From the perspective of land urbanization and financing, Zhang and Xu ( 2017 ) found that the rate of land urbanization played a weak role in reducing carbon emissions. Fan et al ( 2017 ) employed the Divisia decomposition method to explore the impact of urbanization on China’s residential carbon emissions from the perspective of collection and decomposition.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, land finance stimulates an increasing academic interest. In the context of China's special land and fiscal systems, land has become the most important asset of local governments [11]. It has also become an important financing vehicle to China's economy with the commercialization of housing and the marketization of land [1].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Meanwhile, environmental regulations and technological innovation will reduce carbon emissions. Zhang and Xu took 10 years of data from China as a sample and adopted the STIRPAT model to empirically test if the urbanization of the land and the economy had significantly impacted carbon emissions; they found the urbanization rate of land tended to reduce carbon emissions [17]. Ali, et al took 45 years of Singapore data and used an auto-regressive distributed lag model to conclude that urbanization inhibited the impact of carbon emissions in Singapore and that urbanization improved environmental quality by reducing carbon emissions [18].…”
Section: Literature Reviewmentioning
confidence: 99%